A novel monoclonal IgG1 antibody specific for Galactose-alpha-1,3-galactose questions alpha-Gal epitope expression by bacteria - Kreft, Luisa; Schepers, Aloys; Hils, Miriam; Swiontek, Kyra; Flatley, Andrew; Janowski, Robert; Mirzaei, Mohammadali Khan; Dittmar, Michael; Chakrapani, Neera; Desai, Mahesh S.; Eyerich, Stefanie; Deng, Li; et al. (Frontiers in Immunology, 2022)
The alpha-Gal epitope (α-Gal) with the determining element galactose-α1,3-galactose can lead to clinically relevant allergic reactions and rejections in xenotransplantation. These immune reactions can develop because humans are devoid of this carbohydrate due to evolutionary loss of the enzyme α1,3-galactosyltransferase (GGTA1). In addition, up to 1% of human IgG antibodies are directed against α-Gal, but the stimulus for the induction of anti-α-Gal antibodies is still unclear. Commensal bacteria have been suggested as a causal factor for this induction as α-Gal binding tools such as lectins were found to stain cultivated bacteria isolated from the intestinal tract. Currently available tools for the detection of the definite α-Gal epitope, however, are cross-reactive, or have limited affinity and, hence, offer restricted possibilities for application. In this study, we describe a novel monoclonal IgG1 antibody (27H8) specific for the α-Gal epitope. The 27H8 antibody was generated by immunization of Ggta1 knockout mice and displays a high affinity towards synthetic and naturally occurring α-Gal in various applications. Using this novel tool, we found that intestinal bacteria reported to be α-Gal positive cannot be stained with 27H8 questioning whether commensal bacteria express the native α-Gal epitope at all.